Pengaruh Harga, Ulasan Konsumen, dan Pelayanan terhadap Keputusan Pembelian Pakaian Wanita di TikTok Shop - Novera Andri Budiono; Suprayitno Suprayitno (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
The rapid growth of social commerce has transformed consumer purchasing behavior, particularly on platforms such as TikTok Shop that integrate entertainment content with instant transactions. In the fashion sector, purchasing decisions are influenced not only by visual appeal but also by economic and relational factors. This study aims to examine the effects of price, consumer reviews, and service quality on women’s purchasing decisions for clothing products on TikTok Shop. A quantitative associative approach was employed. Data were collected through an online questionnaire distributed to 127 female consumers in Surakarta who had previously purchased clothing via TikTok Shop, selected using accidental sampling. The data were analyzed using multiple linear regression after meeting classical assumption requirements. The findings indicate that price, consumer reviews, and service quality each have a positive and significant effect on purchasing decisions, both partially and simultaneously. Among the examined variables, price demonstrates the strongest contribution to purchasing decisions. These results highlight the importance of competitive pricing, credible online reviews, and responsive service management in strengthening consumer confidence and encouraging purchase decisions in social commerce environments.